Bilateral thalamic infarcts presenting oculomotor nerve palsy: case report - Ramineni, Hari Babu; Mukiri, Seshabala; Jammula, Poornima; Suryadevara, Vidyadhara (International Journal of Research in Medical Sciences, 2017)
Bilateral thalamic infarctions are rare; oculomotor nerve palsy can be the result of direct or indirect damage to the oculomotor nerve. We report a case of oculomotor nerve palsy associated with changes in visual pattern and speech disturbances. There is no loss of consciousness. A computed tomography scan of brain showed acute bilateral thalamic infarct. Oculomotor nerve palsies with pupillary involvement warrant thorough investigation and there is no treatment to re-establish function of the weak nerve other than the body’s own healing process.